Online Business-to-Business Communication and Online Relationship: The Mediator Role of Trust - Guerreiro, J.; Marques, C.; Vilas Boas, A.F. (48th EMAC Annual Conference May 28 – 31, 2019, 2019)
The main purpose of this study is to examine the influence of online personalised content and interactive content communication on online relationship through trust as an affective mediator in a Business-to-Business (B2B) context. A quantitative research approach was conducted using structural equation modelling and a sample of B2B reseller market of information technology in Portugal. Results indicate that online communication influences positively online relationship through trust. Interactive content has a strong influence on trust, whereas the personalised content revealed a weak relationship with trust and, indirectly, with online relationship. Trust has an important role in the relationship as it is a full mediator. In addition, the interactive content is more influential than the personalised content in building and maintaining online relationships in the B2B reseller market.